ECOLOGICAL CONDITION OF AGROLANDSCAPES IN THE MIDDLE ZARAFSHAN BASIN - Yarashev Quvondiq Safarovich; Ulug‘murodov Elmurod Berdimurod o‘g‘li, (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
The article describes the natural and anthropogenic factors affecting the ecological condition of the agrolandscapes of the Middle Zarafshan basin. Also, the state of land reclamation, the level of salinity and their distribution by districts, the good, satisfactory and unsatisfactory state of land reclamation of irrigated lands were studied, and a map of soil salinity was created using geographic information systems.